Analisis Usaha Jamur Tiram sebagai Peluang Bisnis Berkelanjutan untuk Meningkatkan Pendapatan Petani - Azura, Nira; Yohana, Yohana; Sahabudin, Sahabudin (Tirai Edukasi : Jurnal Pendidikan, 2025)
This study aims to analyze oyster mushroom farming as a sustainable business opportunity to increase farmers’ income in Lebah Sempaga Village, Narmada District, West Lombok Regency. The background of this research is the dependence of rural communities on seasonal agriculture, which is vulnerable to climate change and market price fluctuations. A descriptive qualitative approach was employed, using observation, interviews, and documentation. The results indicate that oyster mushroom cultivation has promising prospects since it is not season-dependent, provides significant economic benefits, and utilizes organic waste as a growing medium. Farmers’ income increased from IDR 48,000,000 in 2020 to IDR 56,000,000 in 2024. Main challenges include limited raw materials, lack of capital, and marketing constraints. The findings suggest that with improved farmer capacity, capital access, and market networks, oyster mushroom cultivation can be a sustainable solution to enhance farmers’ welfare.